Uncommon presentation of a complicated jejunal diverticulum: hemoperitoneum and acute abdomen - Lucendo Ramírez, Jesús; Soler Ferriz, Vicente; Vicente López, Marta; Vives Manjón, Cristina (Cirugía del Uruguay, 2025)
Jejunal diverticula, more common in men and elderly patients, are usually asymptomatic and they are therefore often diagnosed incidentally during an imaging test ordered for another reason. Just in an approximately 10% of cases they present as an acute complication, including diverticulitis, intestinal occlusion, or lower gastrointestinal bleeding. For the diagnosis of these complications, performing an abdomino-pelvic Computed Tomography (CT) scan with intravenous contrast is essential. Although conservative management may be used in some favorable contexts, urgent surgery will be necessary in situations of hemodynamic instability or acute abdomen. We present the case of a patient who arrived the hospital with tachycardia, an acute abdomen, and elevated acute phase reactants in the blood test. The CT scan showed a 14-cm collection in close contact with a loop of small intestine, with air inside, suggestive of intestinal perforation. An urgent surgery was decided to be carried out in which a hemoperitoneum secondary to a complicated jejunal diverticulum was seen, with internal bleeding and abundant clots inside it and in the abdominal cavity. Thus, an acute abdomen as a consequence of a hemoperitoneum secondary to a complicated jejunal diverticulum is unusual, and an early suspect is key to avoid diagnostic and therapeutic delays that could increase the patient's morbidity and mortality.